A solar charging system for a portable electric skateboard - Nur Fatin Syahira, Rozak (2017)
In recent decades skateboarding has expanded from recreation into a form of transportation, by customizing a conventional skateboard into an electric skateboard. This project present the design and methodology used in building an electric skateboard that has an alternative solar power charging. The objective of this project are to develop an alternative mode of transport that is highly portable and low cost, high durability and reliable for daily commute with minimum maintenance needed. In this thesis, performance testing of solar charging with the electric skateboard is done to achieve third objective of the project which is to reduce the impact on environment by developing a solar system charger. The results show that electric skateboard can be charged using solar charging system and also normal charge. Moreover it can reduce the environment air pollution. Furthermore, by using solar charging sytem, we can save cost of paying electricity bill when charging the electric skateboard on normal charge since we the system produce their own electricity on off grid solar system. This project also achieve a fast charging with solar system dependent on sun availability and power of battery left to charge the electric skateboard.